Curcuminoids for the Management of Diabetic Macular Edema: A Meta-Analysis Evaluating Effects on Central Macular Thickness and Visual Acuity - Ramzi Amin; Mandy Putriyudi (HM Publisher, 2024)
Diabetic macular edema (DME) is a leading cause of vision loss in diabetic patients, driven primarily by inflammation, oxidative stress, and increased vascular permeability. Current standard therapies, while effective, have limitations. Curcuminoids, derived from Curcuma longa, possess potent anti-inflammatory, antioxidant, and anti-angiogenic properties, suggesting potential therapeutic value in DME. However, clinical evidence requires synthesis. This meta-analysis aimed to evaluate the efficacy of curcuminoid supplementation on Central Macular Thickness (CMT) and Best-Corrected Visual Acuity (BCVA) in patients with DME. A literature search was conducted in PubMed, Embase, Scopus, and the Cochrane Central Register of Controlled Trials (CENTRAL) databases from January 1st, 2013, to December 31st, 2023. We included randomized controlled trials (RCTs) and controlled clinical trials comparing curcuminoid supplementation (as adjunct or monotherapy) against placebo or standard care alone in patients with DME, reporting CMT and/or BCVA outcomes. Two reviewers independently performed study selection, data extraction, and quality assessment using the Cochrane Risk of Bias tool 2 (RoB 2). Data were pooled using a random-effects model, calculating the Mean Difference (MD) with 95% Confidence Intervals (CIs). Heterogeneity was assessed using the I² statistic. Six studies (comprising 388 patients) met the inclusion criteria. The included studies varied in curcuminoid formulations, dosages (ranging from 80 mg to 1500 mg daily), and follow-up durations (3 to 12 months). The overall risk of bias across studies was mixed, with some concerns primarily related to blinding and outcome reporting in several trials. Meta-analysis demonstrated that curcuminoid supplementation was associated with a statistically significant reduction in CMT compared to control groups (MD = -28.54 μm; 95% CI [-45.11, -11.97]; p = 0.0007). Moderate heterogeneity was observed (I² = 62%, p = 0.02). For BCVA (LogMAR), curcuminoid supplementation showed a trend towards improvement, but the result was not statistically significant (MD = -0.04 LogMAR; 95% CI [-0.09, 0.01]; p = 0.11). Heterogeneity for BCVA was low (I² = 15%, p = 0.31). In conclusion, adjunctive curcuminoid supplementation may contribute to a modest but statistically significant reduction in CMT in patients with DME. No statistically significant improvement in BCVA was confirmed, although a favourable trend was observed. Significant heterogeneity in CMT results and methodological limitations in primary studies necessitate cautious interpretation. Larger, well-designed RCTs with standardized, bioavailable curcuminoid formulations and longer follow-up are warranted to definitively establish the clinical role of curcuminoids in DME management.